2014
DOI: 10.1038/cddis.2014.39
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypoxia induces complete antifolate resistance in carcinoma cells due to cell cycle arrest

Abstract: Antifolates have a crucial role in the treatment of various cancers by inhibiting key enzymes in purine and thymidylate biosynthesis. However, the frequent emergence of inherent and acquired antifolate resistance in solid tumors calls for the development of novel therapeutic strategies to overcome this chemoresistance. The core of solid tumors is highly hypoxic due to poor blood circulation, and this hypoxia is considered to be a major contributor to drug resistance. However, the cytotoxic activity of antifola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 52 publications
1
50
0
1
Order By: Relevance
“…We have recently shown that a similar mechanism of resistance to cell cycle dependent drugs (including antifolates) occurs in a range of solid tumors under hypoxic conditions. 46 Therefore, we speculate that among the protective responses to DNA replicationdependent drugs (i.e. DXR, AraC and antifolates), the induction of intron 8 PR of FPGS mRNA is clearly present.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We have recently shown that a similar mechanism of resistance to cell cycle dependent drugs (including antifolates) occurs in a range of solid tumors under hypoxic conditions. 46 Therefore, we speculate that among the protective responses to DNA replicationdependent drugs (i.e. DXR, AraC and antifolates), the induction of intron 8 PR of FPGS mRNA is clearly present.…”
Section: Discussionmentioning
confidence: 90%
“…We therefore hypothesize that drug induced down‐regulation of FPGS and subsequent reduction in the intracellular pool of purine and pyrimidine nucleotides, which should eventually lead to cell‐cycle arrest, acts as a defense mechanism against DNA replication‐dependent drugs. We have recently shown that a similar mechanism of resistance to cell cycle dependent drugs (including antifolates) occurs in a range of solid tumors under hypoxic conditions . Therefore, we speculate that among the protective responses to DNA replication‐dependent drugs (i.e.…”
Section: Discussionmentioning
confidence: 94%
“…Hypoxia‐induced cell cycle arrest is one of the main contributors for chemotherapy resistance and has been studied for many years. Because most anticancer drugs are effective against rapidly dividing cells, hypoxia‐induced cell cycle arrest renders cells insensitive to antitumor agents 39. To confirm that alleviation of hypoxia could modulate hypoxia‐induced cell cycle arrest, the cell cycle of cells from tumor tissue after HBO were studied.…”
Section: Resultsmentioning
confidence: 99%
“…Low oxygen pressure promotes cell cycle arrest (Raz et al, 2014;Semenza, 2011a). HIF-1 binds to the promoter and activates transcription of the MXI1 gene, which encodes a repressor of cMyc transcriptional activity .…”
Section: Oxygen Tension Hypoxia Inducible Factors and Ageing Relatedmentioning
confidence: 99%